Cryptocurrencies and the future of money. Money and trust in Brazil - Seiferling, Mike; Ahmed, Thamin; ElBahrawy, Abeer Yehia; Chan, Keith; Padilha, Tales (IE Center for the Governance of Change, 2020)
Fiat money has had a complicated history in Latin America. Still, Brazil can be considered one of the success stories of the region. Because of mismanagement of government finances, Brazil faced a period of hyperinflation in the late 80s and early 90s. Different orthodox and unorthodox plans were attempted from 1986 to 1991, with no success in tackling inflation. Finally, in 1994 when inflation was hitting 5000% a year, a group of economists working in the ministry of finance managed to implement the ‘Plano Real’ and give credibility to its currency, the Brazilian Real. Since 1994, Brazil has lived a period of stability from a currency perspective and trust in the central bank. The country has now lived for more than 25 years of fairly stable inflation and the Brazilian Real still maintains the same denomination that it had in 1994, making the it the longest living currency the country has had since its imperial money.
Keywords: Cryptocurrency; Criptomonedas; Policies; Políticas; Perspectives; Perspectivas; Disrupting economy; Economía disruptiva